The Public Relations Strategy of The West Java Provincial Education Office in Forming A Positive Image of Institutions: Case Study on Public Relations of West Java Province Education Office - Dinar Binugraheni; Oji Kurniadi (Bandung Conference Series: Public Relations, 2022)
Abstract. in supporting the success of a predetermined plan, public relations of an organization or government agency requires the right strategy in order to achieve the intended target. In this study, we will discuss the "Public Relations Strategy of the West Java Provincial Education Office in Forming a Positive Image Agency (Case Study on the Public Relations of the Education Office). The purpose of this study was to determine the activities/work programs and communication strategies used by the West Java Provincial Education Office in forming a positive image and to find out what the obstacles were and how to overcome them. This study uses a qualitative research method with a case study approach, namely by examining the questions and problems that exist in a study. The subjects of this study were 4 people who were the head of public relations, public relations staff, school principals and high school students. Data collection techniques by means of interviews, documentation and literature study. Data analysis techniques are by reducing data, presenting data, and conclusions and levers. The validity tests carried out by researchers in this study were triangulation of sources, using reference materials, and increasing persistence. The results of this study are the West Java Provincial Education Office has several work programs that are considered to be able to form a positive image such as protocol, making magazines, managing E-Clip, Lapor and Zimbra Mail websites and coverage, besides that communication strategy is one of the important factors in shaping the image. The communication strategy used by the public relations of the West Java Provincial Education Office such as maintaining communication patterns such as interpersonal communication, group communication and mass communication as well as maintaining openness and information provided to the public can affect the image of the West Java Provincial Education Office. The inhibiting factors of public relations in forming the image consist of 3 factors, namely internal factors, external factors and substance factors. Internal factors such as the difficulty of adapting to the digital era, external factors such as the creation of misunderstandings with the media and substance factors such as the lack of attention from superiors in facilitating supporting facilities for the Public Relations of the West Java Provincial Education Office. Abstrak. Abstrak. Dalam menunjang keberhasilan sebuah rencana yang telah ditetapkan, humas sebuah perusahaan atau instansi pemerintahan memerlukan strategi yang tepat agar mencapai sasaran yang dituju. Dalam penelitian ini akan dibahas mengenai “Strategi Humas Dinas Pendidikan Provinsi Jawa Barat Dalam Membentuk Citra Positif Instansi (Studi Kasus Pada Humas Dinas Pendidikan). Tujuan dari penelitian ini adalah untuk mengetahui kinerja dan strategi komunikasi yang digunakan humas Dinas Pendidikan Provinsi Jawa Barat dalam membentuk citra positif serta mengetahui apa saja faktor pendukung dan penghambatnya. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus, yaitu dengan cara menguji pertanyaan dan masalah yang ada dalam sebuah penelitian. Subjek dari penelitian ini yaitu 4 orang yang merupakan kepala dan staff humas Dinas Pendidikan Provinsi Jawa Barat. Teknik pengumpulan data dengan cara wawancara, dokumentasi dan studi kepustakaan. Teknik analisis data yaitu dengan cara mereduksi data, penyajian data, dan membuat kesimpulan serta verifikasi. Uji keabsahan yang dilakukan peneliti dalam penelitian ini adalah triangulasi sumber, menggunakan bahan referensi, dan meningkatkan ketekunan.